Additional Criminals To Corporations As An Efforts To Create Criminal Impact With Decision - Kukuh Dwi Kurniawan; Fitria Esfandiari (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
Corporations are always a problem when asked for criminal responsibility. In addition to their own separate ways, separate regulations are needed to examine and prosecute corporations that carry out criminal acts. Like the case that has occurred, the KPK has positioned PT NKE as a legal subject to hold criminal liability. Prosecutors prosecute, and necessary crimes also provide additional penalties for a ban on participating in state auctions for six months. The study was conducted in a descriptive analysis and literature review approach. This study examined philosophically historically the existence of additional crimes to provide a conviction that pledged perpetrators. The conclusion that can be obtained from studying different criminal offences other than the main criminal to the corporation as a legal breakthrough in conducting regular excavation from existing regulations to create a criminal punishment that has a deterrent effect on the corporation that commits a criminal offence.Keywords: Additional Crimes; Corporations; Deterrent Effects. AbstrakKorporasi selalu menjadi masalah ketika dimintai pertanggungjawaban, selain diperlukan cara tersendiri juga diperlukan regulasi tersendiri dalam upaya memeriksa dan mengadili korporasi yang melaklukan tindak pidana. Seperti kasus yang telah terjadi, KPK telah memposisikan PT NKE sebagai subyek hukum sehingga dapat dimintai pertanggugjawaban pidana. JPU melakukan penuntutan selain pidana pokok juga memberikan pemidanaan tambahan berupa larangan mengikuti lelang negara selama enam bulan. Penelitian dilakukan secara deskriptif analisis dan pendekatan kajian pustaka serta dalam penelitian ini mengkaji secara historis filosofis adanya pidana tambahan sehingga dapat memberikan pemidanaan yang menjera pelaku. Kesimpulan yang dapat diperoleh dari penelitian penjatuhan pidana tambahan selain pidana pokok kepada korporasi sebagai upaya terobosan hukum dalam melakukan penggalian hukum dari peraturan yang telah ada untuk menciptakan pemidanaan yang memiliki efek jera kepada korporasi yang melakukan tindak pidana.Kata Kunci: Pidana Tambahan; Korporasi; Efek Jera.